Kuat Tekan Dan Sorptivity Beton Abu Terbang Dengan Perawatan Wet-Dry Di Air Gambut - Fitri Amelia; Monita Olivia; Iskandar Romey Sitompul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study examines the compressive strength and sorptivity of PCC concrete and PCC-FA concrete subjected to the exposure of peat water. The specimens were treated with two different, namely static and wet-dry exposure. In the static exposure, the sample were curedcontinuously in the peat water at the age of 7 and 28 days. In the wet-dry exposure, the samples were put in the cycles of wet and dry during the curing by using peat water. Fly ashwas used to increase the compressive strength and sorptivity of concrete during wet-dry cycles immersion since the wet-dry cycle in peat water is considered as the worst environmental condition that can affect the strength of concrete. The compressive strength ofPCC (static), PCC-FA (static) and PCC-FA (wet-dry) were increased at 28 days immersion in peat water, respectively by 7.24%, 20.45% and 12.89%. The compressive strength of PCC(wet-dry) decreased at 28 days immersion in peat water by 4.31%. The sorptivity was inversely proportional to the results of compressive strength. Based on the test results, it wasconcluded that the use of fly ash in concrete that experiences a wet-dry constant state could improve the quality of concrete if immersed in peat water.Keywords : Fly ash concrete, fly ash, wet-dry cycles, peat water, PCC.